LUNFARDO LEXICAL UNITS RELATED TO LEGAL MATTERS - NOWAK, Joanna (Comparative Legilinguistics, 2017)
The article deals with the Argentinian slang Lunfardo which is spoken mainly in Buenos Aires, La Plata and their surroundings. The main objective of the paper is the lexicological analysis of Lunfardo lexical units related to legal matters. Lunfardo came into existence at the turn of the 19th and 20th centuries when a great amount of immigrants from different European countries came to Argentina, mainly to its capital Buenos Aires. The languages and dialects spoken by immigrants started to mix with Spanish (its Argentinian variant) and Lunfardo started to develop. The article investigates the history of this linguistic phenomenon and its present situation. It tries to characterize Lunfardo focusing on its linguistic features and social background of its users.